A arquitetura moderna religiosa brasileira: nas revistas Acrópole e Habitat entre os anos de 1950 a 1971 - Avelar, Ana Paula Borghi de (2017)
This dissertation had as objective to make a survey of documentary data concerning the Brazilian modern religious architecture within Brazilian periodicals specialized in architecture, being they Acropolis and Habitat, magazines from São Paulo, from 1950 to 1971. The temporal cut made takes into account the boom of modern Brazilian architecture and the beginning of Habitat magazine until the closure of the activities of both Habitat (1965) and Acropolis (1971). For this, we analyze the presentation of these publications as well as the number of published projects and the characteristics of the Brazilian modern architecture, presented in these projects, for the analysis we adopted the Panofsky methodology, referring to iconography and iconology. The choice of this theme took into account the importance of religious spaces for society and for Brazilian architecture, not only for the use of innovative techniques and new materials, but also for the rupture with previous trends and the importance it had for the formation of an identity national. In the religious field, modern Brazilian architecture began with the Pampulha Chapel in 1943, the work of the architect Oscar Niemeyer, which broke with everything that had been used until then for a Catholic temple, bringing a structure used by hangars and bridges for cover of a church, completely innovating Brazilian architecture making the reinforced concrete plastic subject to unusual forms. Based on all its significance for the architectural field the Pampulha Chapel was listed with only three years of construction being the first modern building inscribed in the book of Tombo of the Fine Arts. Giving freedom of creation to modern architects, who, even in the midst of much discussion with the Church, were able to exploit to the full the characteristics of modern architecture by producing a collection of beautiful designs, many of which were recorded by the magazines.